Experience of long-term belimumab use in patients with systemic lupus erythematosus (a case report) - Natalia Gennadyevna Klyukvina (Современная ревматология, 2013)
In the past years considerable progress has been made in the treatment of systemic lupus erythe-matosus; however, not all questions have been answered. The range of medications has substan-tially increased. The paper describes a case of the long-term use of the new genetically engineered agent belimumab in a patient with systemic lupus erythematosus.